Synergy in combining findings from mammography and ultrasonography in detecting malignancy in women with higher density breasts and lesions over 2 cm in Albania - Malaj, Altin; Shahini, Albana (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : To provide evidence of the synergy of combining findings from mammography (MM) and ultrasonography (US) in detecting malignancy in women with high-density breasts. Material and methods: A total of 245 women were screened for breast cancer using both mammography and ultrasonography at the American Hospital in Tirana during 2013–2014. The data was used to identify possible benefits in detecting malignancy, by combining the findings of MM and US and confirming them with those of the biopsy. Data on age, breast density, BI-RADS classification, and biopsy confirmations were collected and analysed. Results : Out of the 245 women, 36 biopsies were taken (17 for women classified BI-RADS 4 and 5; 19 for women with BI-RADS 3 that had grown in size from the previous examination). The accuracy in detecting malignancy for low-density-breast women was 90% for MM, 70% for US, and 90% for combined. For high-density breasts, the accuracy was 65% for MM, 79% for US, and 82% for combined findings. Multivariate analysis indicates that high-density-breast women who have a malignant finding in at least one of the examinations (MM or US) are 24 times more likely (p = 0.039) to have a positive finding in biopsy for malignancy. The odds increased 32 times for lesions over 2 cm (p = 0.056). Conclusions : Our study results indicate additional benefits of combining findings from MM and US for high-density-breast women. Further study is warranted in a larger population and for different kinds of cancer.